Réponses

  • Utilisateur Brainly
2014-04-02T16:39:31+02:00
1) 
A= 3x(2-4x)
A= 6x-12x²
A= -12x²+6x

B= (4x-3)(2x+1)
B= 8x²+4x-6x-3
B=8x²-2x-3

C= (3x-7)(5-2x)
C= 15x-6x²-35+14x
C= -6x²+29x-35

D= -5(-2x+3x-7)-(x+3)(4-3x)
D= (-10x-15x+35)-(4x-3x²+12-9x)
D= -25x+35-4x+3x²-12+9x
D= 3x²-20x+23

2) 
E= 5x+25
E= 5(x+5)

F= 16x²-18x

G= 4a²-6ab+10a
G= 2a(2a - 3b +5) 

H= (x-2)(5x+1)+(x+2)(x-3)
H= (x-2)*[(5x+1)+(x-3)]
H= (x-2)(4x-3)

I= (2x+1)²-(2x+1)(2x-5)
I= (2x+1)*[(2x+1)-(2x-5)]
I= (2x+1)(0x+6)

J= 4x²-4x+1
J = 4x²-4x+1 - (2x-1)(3x-2) 
J = (2x-1)² - (2x-1)(3x-2) 
J = (2x-1)((2x-1)-(3x-2)) 
J = (2x-1)(2x-1-3x+2) 
J = (2x-1)(-x+1)

K= 100-64t²

L= 36a²+108a+81
L= (6a+9)(6a-9)